Get the information you need from a community of experts on IDNLearn.com. Get accurate and timely answers to your queries from our extensive network of experienced professionals.
Sagot :
Certainly! Let's work through the problem step-by-step.
We are given the following functions:
[tex]\[ f(x) = 3x + p \][/tex]
[tex]\[ g(x) = px + 4 \][/tex]
We also know that:
[tex]\[ f(g(x)) = 6x + q \][/tex]
First, let’s determine [tex]\( f(g(x)) \)[/tex].
1. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
First, we find [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = px + 4 \][/tex]
Now substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(px + 4) \][/tex]
2. Evaluate [tex]\( f(px + 4) \)[/tex]:
Using the expression for [tex]\( f(x) \)[/tex]:
[tex]\[ f(px + 4) = 3(px + 4) + p \][/tex]
3. Expand and simplify:
[tex]\[ f(px + 4) = 3(px) + 3(4) + p \][/tex]
[tex]\[ f(px + 4) = 3px + 12 + p \][/tex]
4. Set this equal to the given expression for [tex]\( f(g(x)) \)[/tex]:
We know from the problem statement:
[tex]\[ f(g(x)) = 6x + q \][/tex]
Therefore,
[tex]\[ 3px + 12 + p = 6x + q \][/tex]
5. Equate the coefficients of [tex]\( x \)[/tex] and the constant terms:
By comparing the coefficients of [tex]\( x \)[/tex] on both sides of the equation,
[tex]\[ 3p = 6 \][/tex]
Solving for [tex]\( p \)[/tex]:
[tex]\[ p = \frac{6}{3} \][/tex]
[tex]\[ p = 2 \][/tex]
6. Substitute [tex]\( p = 2 \)[/tex] into the constant term equation:
Now we substitute back into the equation for the constants,
[tex]\[ 12 + p = q \][/tex]
Substitute [tex]\( p = 2 \)[/tex]:
[tex]\[ 12 + 2 = q \][/tex]
[tex]\[ q = 14 \][/tex]
Therefore, the values of the constants are:
[tex]\[ p = 2 \][/tex]
[tex]\[ q = 14 \][/tex]
This completes the step-by-step solution to the problem.
We are given the following functions:
[tex]\[ f(x) = 3x + p \][/tex]
[tex]\[ g(x) = px + 4 \][/tex]
We also know that:
[tex]\[ f(g(x)) = 6x + q \][/tex]
First, let’s determine [tex]\( f(g(x)) \)[/tex].
1. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
First, we find [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = px + 4 \][/tex]
Now substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(px + 4) \][/tex]
2. Evaluate [tex]\( f(px + 4) \)[/tex]:
Using the expression for [tex]\( f(x) \)[/tex]:
[tex]\[ f(px + 4) = 3(px + 4) + p \][/tex]
3. Expand and simplify:
[tex]\[ f(px + 4) = 3(px) + 3(4) + p \][/tex]
[tex]\[ f(px + 4) = 3px + 12 + p \][/tex]
4. Set this equal to the given expression for [tex]\( f(g(x)) \)[/tex]:
We know from the problem statement:
[tex]\[ f(g(x)) = 6x + q \][/tex]
Therefore,
[tex]\[ 3px + 12 + p = 6x + q \][/tex]
5. Equate the coefficients of [tex]\( x \)[/tex] and the constant terms:
By comparing the coefficients of [tex]\( x \)[/tex] on both sides of the equation,
[tex]\[ 3p = 6 \][/tex]
Solving for [tex]\( p \)[/tex]:
[tex]\[ p = \frac{6}{3} \][/tex]
[tex]\[ p = 2 \][/tex]
6. Substitute [tex]\( p = 2 \)[/tex] into the constant term equation:
Now we substitute back into the equation for the constants,
[tex]\[ 12 + p = q \][/tex]
Substitute [tex]\( p = 2 \)[/tex]:
[tex]\[ 12 + 2 = q \][/tex]
[tex]\[ q = 14 \][/tex]
Therefore, the values of the constants are:
[tex]\[ p = 2 \][/tex]
[tex]\[ q = 14 \][/tex]
This completes the step-by-step solution to the problem.
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com is your source for precise answers. Thank you for visiting, and we look forward to helping you again soon.